Analysis of Electric Field and Current Density Characteristics of HVDC XLPE Insulator with Effect of Arsenic - Hassan, Nurul Shahirah; Mohd Jamail, Nor Akmal (Evolution in Electrical and Electronic Engineering, 2022)
An insulator is one of the important things in high voltage technology. The insulator quality should be a top priority when choosing an insulator for cable either overhead or underground because an unsuitable insulator can lead to insulator breakdown and other big problems. XLPE insulator cable is the most popular insulator in high voltage technology because it has high-temperature resistance and aging resistance compared to other insulators. Besides, electric field and current density are very important characteristics in the insulation process. Flashover can occur if the electric field and current density are increasing and cause expediting the insulator premature aging process. Arsenic is known as soil and underground contaminants. This research is to identify the effect of arsenic on electric field and current density by using FEMM Software. The software is used to simulate the XLPE insulator cable model with different thicknesses of arsenic. The result showed that the electric field strength and current density are inversely proportional to the thickness of arsenic. As a conclusion, the electric field strength and current density are decreased when the thickness of arsenic is increased.